DIFFERENCE IN POST-HARVEST PROCESSING ON COFFEE FLAVOR PREFERENCE: English - Bumi, Salsabila; Kurniaditya, Viki; Rizkaprilisa, Windy; Luwidharto, Joshua (Fakultas Sains dan Teknologi, Universitas Nasional Karangturi, 2025)
Coffee is one of the most popular products among consumers, mainly due to its unique flavor profile. Several factors, including plant variety, environmental conditions, and postharvest processing methods, determine this uniqueness. Post-harvest processing, which involves the transformation of coffee beans from cherries to roasted beans, significantly affects the taste, aroma, and body of the coffee. Processing methods such as the wet (full washed) and dry (natural) processes produce distinct flavor characteristics. The wet process tends to yield a clean taste with a bright acidity, while the dry process emphasizes sweetness and fruit complexity. Understanding the impact of these processing methods is essential for coffee producers and the industry to create high-quality products that align with consumer preferences.